The Organisation for Economic Co-operation and Development's International Early Learning Study: Opening for debate and contestation. (September 2016) - Moss, Peter; Dahlberg, Gunilla; Grieshaber, Susan; Mantovani, Susanna; May, Helen; Pence, Alan; Rayna, Sylvie; Swadener, Beth Blue; Vandenbroeck, Michel
The Organisation for Economic Co-operation and Development is initiating the International Early Learning Study, a cross-national assessment of early learning outcomes involving the testing of 5-year-old children in participating countries. The authors use this colloquium to inform members of the early childhood community about this project and to raise concerns about its assumptions, practices and possible effects. The authors also invite readers' comments, to start a process of democratic dialogue and contestation.